2021
DOI: 10.34237/1008927
|View full text |Cite
|
Sign up to set email alerts
|

2020 hurricane impact assessment for the northern Gulf of Mexico: Hurricane Sally and Hurricane Zeta

Abstract: Regional-scale shoreline and beach volume changes are quantified using the Joint Airborne Lidar Bathymetry Technical Center of Expertise’s digital elevation model products in a change detection framework following the passage of the two landfalling hurricanes, Hurricanes Sally and Zeta, along the northern Gulf Coast in late fall 2020. Results derived from this work include elevation change raster products and a standard set of beach volume and shoreline change metrics. The rapid turn-around and delivery of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The characteristic westward‐directed longshore sand transport in the northern Gulf of Mexico is disrupted by the ebb tidal delta, including Sand Island, in addition to the dredged Mobile Bay shipping channel (Byrnes et al., 2013; Cipriani & Stone, 2001; Dzwonkowski et al., 2015), potentially creating a sand deficit just to the west of the ebb tidal delta (Morton, 2008; Otvos & Carter, 2008). Additionally, post‐Sally Lidar bathymetry surveys showed a loss of 9.38 × 10 3 m 3 of sand along a 183 m‐long transect near W05 since 2016 (McGill et al., 2021). Furthermore, cores collected near W05 in previous studies revealed thin (as little as <25 cm) shoreface sand layers overlying relict estuarine muddy sands and sandy muds deposited several thousand years ago during lower sea level (Hollis et al., 2019); this was consistent with the cores collected for this study, which displayed sand over grayish mud (Figure S5a in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic westward‐directed longshore sand transport in the northern Gulf of Mexico is disrupted by the ebb tidal delta, including Sand Island, in addition to the dredged Mobile Bay shipping channel (Byrnes et al., 2013; Cipriani & Stone, 2001; Dzwonkowski et al., 2015), potentially creating a sand deficit just to the west of the ebb tidal delta (Morton, 2008; Otvos & Carter, 2008). Additionally, post‐Sally Lidar bathymetry surveys showed a loss of 9.38 × 10 3 m 3 of sand along a 183 m‐long transect near W05 since 2016 (McGill et al., 2021). Furthermore, cores collected near W05 in previous studies revealed thin (as little as <25 cm) shoreface sand layers overlying relict estuarine muddy sands and sandy muds deposited several thousand years ago during lower sea level (Hollis et al., 2019); this was consistent with the cores collected for this study, which displayed sand over grayish mud (Figure S5a in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%
“…The clean sands at the middle and eastern 5 m sites (M05 and E05) may have been resuspended and redeposited with little transport, had additional sand deposition, or been replenished by alongshore transport with sand eroded from the beach and/or shoreface from the east, resulting in no apparent net loss of sand from these sites (Keen et al, 2012;Mclaren, 1981). Given the strong near-bed currents observed at 20 m (CP) in addition to slight fining of M05 sands (Figures 2d,4c,and 4d,Figure S4 in Supporting Information S1), sand replenishment from alongshore transport seemed more likely than resuspension with little sand movement at 5 m. Lidar bathymetry surveys shortly after Sally (late September-early October 2020) revealed additional evidence of sand transport, as 2.81 × 10 4 m 3 of sand was lost from a 183 m-long alongshore transect since 2018, which included the location of E05 (McGill et al, 2021). M05 was also located on the Mobile Bay ebb tidal delta and likely experienced frequent sand movement via tidal exchange (e.g., Hummel & Smith, 1996).…”
Section: Spatially Variable Storm Beds Following Hurricane Sallymentioning
confidence: 99%